Echocardiographic parameters of myocardial work in relation to prolonged strenuous physical exercise. (14th October 2021) - Erevik, C; Kleiven, Ø; Froysa, V; Bjorkavoll-Bergseth, M; Hansen, M; Chivulescu, M; Klaboe, L G; Dejgaard, L; Skadberg, O; Melberg, T; Urheim, S; Haugaa, K; et al.
Abstract: Background: Myocardial work (MW) assessed by echocardiography is a novel measure of left ventricular (LV) function. This measure is load-independent, and therefore a more accurate method for assessing LV function when there are changes in loading conditions. The purpose of this study was to examine alterations in MW parameters, blood pressure (BP) and LV global longitudinal strain (LV GLS) in relation to strenuous exercise, and to compare the response between two different physical stress situations. Methods: 59 healthy recreational athletes were assessed by echocardiography before-, immediately- and 24 hours after two episodes of high-intensity endurance exercise. The first exercise was a cardiopulmonary exercise (CPX) test, which included both a stepwise lactate threshold- and a maximal oxygen uptake test. The second exercise was a 91-km mountain bike leisure sport cycling competition. Global work index (GWI), global constructive work (GCW), global wasted work (GWW) and global work efficiency (GWE) were estimated from LV pressure-strain loops, constructed from a combination of LV GLS and non-invasive BP, using commercially available software package (Echopac V.202, GE). Results: Subjects were 52 (43–59) years old (73% men). The duration of the CPX-test was 43 (40–45) minutes, and the race was 230 (210–245) minutes. The average heart rate during the CPX-test and the race was 144 (140–153) and 154 (148–161) beats per minute (bpm), respectively. The relative changes (percent) in systolic blood pressure (SBP) and LV GLS compared with pre-exercise values are demonstrated in Figure 1a, and GWI and GCW compared with pre-exercise values in Figure 1b. GWI at baseline was 2156 (1899–2400) mmHg% and GCW 2383 (2152–2668) mmHg%. There was a significant reduction in LV GLS (p=0.015), SBP, GWI and GCW following the CPX-test and the race (p<0.001), while there was an increase in heart rate and cardiac output (p<0.001). After the race, there was a significant (p=0.001) increase in GWW, and a reduction (p=0.006) in GWE. Conclusion: There was a significant reduction in GWI and GCW after both the CPX-test and the race, suggesting that these markers reflect increased myocardial exhaustion following strenuous physical exercise. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This work was supported by ConocoPhillips and the Simon Fougner Hartmann Trust